PERLINDUNGAN HUKUM BAGI PARA PIHAK DALAM PERJANJIAN BANGUN BAGI YANG DIBUAT DIHADAPAN NOTARIS - AHMAD BUCHORI ANANDA NASUTION (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Muhd. Yamin2. T. Keizerina Devi A3. Notaris Suprayitno The position of the deed of the authority to sell in build-operate transfer contract is a part of the contract which cannot be independent. The authority to sell can be given before and after the construction has been done in condition that both parties agree to use the deed of the authority to sell. The legal protection for the land owner in the implementation of a build-operate transfer contract is by conducting prevention through an agreement of both parties by including a clause which provides legal protection for them in using the deed of the authority to sell.Keywords: Stakeholders, Legal Protection, Build-Operate Transfer Contract